1999
DOI: 10.1037/0022-3514.76.6.893
|View full text |Cite
|
Sign up to set email alerts
|

The chameleon effect: The perception–behavior link and social interaction.

Abstract: The chameleon effect refers to nonconscious mimicry of the postures, mannerisms, facial expressions, and other behaviors of one's interaction partners, such that one's behavior passively and unintentionally changes to match that of others in one's current social environment. The authors suggest that the mechanism involved is Has. perception-behavior link, the recently documented finding (e.g., J. A. Bargh, M. Chen, & L. Burrows, 1996) that the mere perception of another's behavior automatically increases the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

119
3,020
25
60

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 3,441 publications
(3,224 citation statements)
references
References 93 publications
(114 reference statements)
119
3,020
25
60
Order By: Relevance
“…Responsiveness and synchrony in turn tend to increase positivity (Chartrand & Bargh, 1999). Insko and Wilson (1977) demonstrated that responsiveness during interaction increases liking.…”
Section: Responsiveness and Synchronymentioning
confidence: 97%
“…Responsiveness and synchrony in turn tend to increase positivity (Chartrand & Bargh, 1999). Insko and Wilson (1977) demonstrated that responsiveness during interaction increases liking.…”
Section: Responsiveness and Synchronymentioning
confidence: 97%
“…Interpersonal synchrony has been suggested to impact the quality of social exchanges (Chartrand and Bargh, 1999), and as such, understanding the social factors mediating synchrony is an important goal for the field. Probing the conditions under which interpersonal synchrony occurs, Miles et al found that when individuals interact with members of an ostensibly different social group (minimally defined by wearing of different color stickers purportedly reflecting their artistic taste), they display more behavioral synchrony than when interacting with members of their own minimal group.…”
Section: Behavioral Coordinationmentioning
confidence: 99%
“…Although understanding of goals requires conscious perception of actions, it is not yet known to what extent activity in the mirror system depends on the degree of conscious perception of an action. Behavioral studies in humans indeed suggest that an unconscious process of imitation takes place during observation of actions performed by others, resulting in an increased tendency to perform similar actions (e.g., social contagion/the chameleon effect, Chartrand and Bargh 1999). Such implicit imitation could be the result of mirror neuron activity (Hogeveen and Obhi 2012; Cross and Iacoboni 2014).…”
Section: Introductionmentioning
confidence: 99%